Industrial engineering student competency mediation model: analysis from the perspective of educational psychology - Iraola Arroyo, Juan Alonso (2023)
This paper proposes a new managerial skill called contextual search, which is the ability to study the national and international socio-economic reality and which is the basis for deci-sion making and planning. Therefore, the objective of this study is to analyze the predictive influence between contextual research, decision making, and planning skills in Industrial Engineering students of a private university in Lima, Peru. The sample included 150 students pursuing an industrial engineering career: 84 men (56%) and 66 women (44%). The age of the participants ranged from 16 to 31 years (mean age 19.77; standard deviation 4.50). The results showed that all three skills were significantly related and predicted simultaneously. Nevertheless, it identified that the decision-making skill mediates the predictive relationship between context finding and planning. Thus, it is understood that future industrial engineers can plan well if they have previously developed the context-finding and decision-making skills.